Mammography perceptions and practices among women aged 30–49: The role of screening programme availability and cultural affiliation. Issue 2 (February 2020) - Labrie, Nanon H.M.; Ludolph, Ramona A.; Schulz, Peter J.
Highlights: Fear of breast cancer induces the motivation to engage in opportunistic screening. Opportunistic screening is prevalent among young Swiss women (30–49). Screening perceptions and practices differ between cultural-linguistic regions. Screening programme availability relates to mammography attitudes, behaviours. This has implications for public health communication about screening. Abstract: Objective: To explore the role of systematic screening programme availability and cultural affiliation as drivers of mammography perceptions/practices among women aged 30–49, who are not eligible for screening. Methods: Cross-sectional survey about mammography perceptions/practices among N = 918 Swiss women (30–49), across three cultural-linguistic regions (Swiss-German, Swiss-French, Swiss-Italian) and 26 cantons. Results: In cantons offering systematic screening programmes, women appeared more likely to ask for a mammogram, felt more susceptible to breast cancer, and perceived more benefits to screening. Swiss-German women engaged less in screening and felt less susceptible to breast cancer than women in other cultural-linguistic regions. Within the Swiss-German region, women living in cantons with programmes were more likely to ask for a mammogram than in cantons without. Conclusions: Programme availability and cultural affiliation both appear related to young women's screening perceptions/practices. While the interaction between these factors should be further explored, this study provides some preliminary evidence that cultural affiliation is the more important driver. Practice Implications: Health communication efforts should consider the impact of these drivers on women's intentions to have a mammogram, prior to the recommended age. Tailored communication – public and interpersonal - should be directed towards facilitating informed decision-making and avoidance of mammography overuse.